A Case of Infective Endocarditis Caused by : Unraveling a Rare Pathogen and Dire Outcome - Divisha Sharma MD; Zoheb I. Sulaiman DO; Patrick J. Tu PharmD; Sean Harrell MD; Stuart Cavalieri MD; Peter J. Skidmore MD; Stephanie L. Baer MD (Journal of Investigative Medicine High Impact Case Reports, 2024)
Citrobacter koseri (formerly classified as Citrobacter diversus ) is a gram-negative bacillus (GNB) that occurs as an opportunistic pathogen in neonates and immunocompromised patients. Citrobacter species have been implicated in nosocomial settings leading to infections involving the urinary tract, respiratory tract, liver, biliary tract, meninges, and even in rarer conditions—blood stream infection and infective endocarditis (IE). Gram-negative bacilli are responsible for 3% to 4% of all IE cases and have been traditionally associated with intravenous drug users. Patients with non-HACEK (species other than Haemophilus species, Actinobacillus actinomycetemcomitans, Cardiobacterium hominis, Eikenella corrodens, or Kinglella species) GNB IE have poor clinical outcomes with higher rates of in-hospital mortality and complications. The American Heart Association (AHA) and Infectious Diseases Society of America (IDSA) both recommend the use of combination antibiotic therapy with a beta-lactam (penicillins, cephalosporins, or carbapenems) and either an aminoglycoside or fluoroquinolones for 6 weeks (about 1 and a half months) to treat IE due to non-HACEK GNB. Citrobacter koseri is becoming more recognized due to its inherent resistance to ampicillin and emerging drug resistance to beta lactams and aminoglycosides requiring carbapenem therapy. Our case is of a 75-year-old male with no previously reported history of primary or secondary immunodeficiency disorders who developed C koseri blood stream infection. His infectious work-up revealed mitral valve IE and septic cerebral emboli resulting in ischemic infarcts. This case illustrates the importance of recognizing GNB organisms as rising human pathogens in IE cases even without active injection drug use or nosocomial exposure.